FAKTOR DETERMINAN PENERAPAN ASUHAN KEBIDANAN HOLISTIC CARE PADA KUNJUNGAN NIFAS (KF) I DI TPMB PERMATA HATI MATESIH - Putri, N. Kadek Sri Eka; Sari, Reni Puspita; Mirasari, Triana (Jurnal Ilmiah Maternal, 2025)
Postpartum blues is a common psychological condition affecting postpartum women worldwide. WHO (2018) reports a global prevalence of 3–8%, with 50% of cases occurring among individuals aged 20–50 years. In Asia, the prevalence is considerably higher, ranging from 26–85% of postpartum women. Holistic postpartum care is essential, covering physical, psychological, social, spiritual, and cultural needs. This study aimed to identify factors associated with holistic midwifery care during the First Postpartum Visit (KF I) at TPMB Permata Hati Matesih. A quantitative descriptive study with a retrospective cohort design was conducted using total sampling. Secondary data from January–December 2024 were collected from TPMB Permata Hati Matesih. Data were analyzed using descriptive statistical methods in Microsoft Excel. A total of 41 respondents were included. Most mothers were aged 20–35 years (80%), were housewives (61%), and were multiparous (61%). All respondents (100%) had a history of vaginal delivery. Educational levels were predominantly intermediate and higher (49%). Cultural factors showed that all respondents (100%) received family and community support during the postpartum period. All mothers (100%) exhibited normal fundal height, firm uterine contractions, and postpartum bleeding <500 cc within the first 24 hours. Several maternal factors, including age, parity, education level, cultural support, and physiological postpartum indicators, were associated with the implementation of holistic midwifery care during the first postpartum visit. Strengthening holistic approaches in postpartum services is essential to support maternal well-being.